Implications of SAFTA for Indian Economy: Trade, Compatibility and Welfare Effects. Issue 4 (November 2019) - Jain, Hansa
Among the members of South Asian Free Trade Area (SAFTA), India dominates in terms of its geographical location, land area, population size and economic share. However, SAFTA is treated as a weak agreement as India is highly outward oriented for trade. This raises a question about India's trade compatibility with South Asian countries. Also since SAFTA is now fully implemented, there is a need to determine its welfare effects for India as well as for the region. The study focuses on (a) trends and patterns of India's intra-regional trade with South Asian countries, (b) trade compatibility and (c) welfare effects of SAFTA for the Indian economy. India's trade intensity, trade share and trade compatibility with the other regional members is calculated. GTAP simulations are used to determine welfare effects. The study is based upon the secondary data. The study finds that with the implementation of SAFTA, India's trade intensity and trade share with its regional members has slightly improved. Trade compatibility though low, is gradually improving. The study considers SAFTA as a positive sum game for India. India is likely to have favourable allocative efficiency effect, terms of trade effect and investment-savings effect if trade facilitation measures are adopted. JEL Codes: F150, F10, F140, C150